Porous gelatin/poly(ethylene glycol) scaffolds for skin cells. Issue 1 (2nd January 2017) - Vahidi, Milad; Frounchi, Masoud; Dadbin, Susan
ABSTRACT: Biocompatible porous polymeric scaffolds provide a suitable environment for proliferation of stem cells in human body. In this research work, porous gelatin – poly(ethylene glycol), PEG, based scaffolds were prepared using combination of freeze-gelation and freeze-extraction methods. Effects of various parameters such as freezing temperature, cross-linking agent, concentrations of gelatin and PEG and their blending ratio on physical and mechanical properties, swelling ratio, porosity, pore size, and degradation rate of scaffolds were investigated. Also, proliferation of fibroblast skin cells on the scaffolds was examined by MTS assay to assess the suitability of the scaffolds in wound healing and skin regeneration. The mean pore diameters of the scaffolds ranged from 100 to 182 µm. The scaffolds with higher PEG content possessed larger pore size. On the contrary, the scaffolds prepared from higher solution concentration had smaller mean pore size, and the pores were mostly interconnected. The latter scaffolds had good mechanical properties. Addition of PEG contributed to softness of the scaffolds as well. The water uptake capacity of the scaffolds was higher with larger pore size and higher pore interconnectivity. The scaffolds were biocompatible with human skin fibroblast cells and showed high growth level of the cells.